Digital marketing communication, social media, competency, and marketing team members in Indonesia - Irmawan Rahyadi (Jurnal Studi Komunikasi, 2024)
The profession of digital marketing in Indonesia with extensive business development is challenging due to the technical skills and practical elements of marketers in the job market. Keeping updated credentials in digital marketing is crucial to reduce the risk of losing competition, as current advancement in the industry requires trained personnel resulting in notable competition, training, and education. This demands trained personnel and places the importances of having these credentials. This study aims to investigate how digital marketers navigate their career paths and explore the composition of digital marketing. This study aims to analyse the dynamics of digital marketing that includes the career path of professionals, qualifications in the industry, and digital marketing education. This research is mostly grounded on data extracted from a qualitative method, which has been gathered based on the experiences from the professionals who have worked in local and international corporations operating in Indonesia. Interviews with professionals employed in national and multinational companies enriched the data. This was analysed using qualitative data analysis techniques. The evidences to date shows that trends in digital marketing practices are unique and homogenous to the country's marketing field. The data and literature report sizes and composition when digital marketing interventions are delivered and adopted. This study also includes the differences between offline marketing practices in collaboration with digital marketing practices to marketing teams, and the application of social media marketing from the company's point of view. Not only small-size companies have noticed a difference in their marketing teams’ dynamic, but big corporations also have experienced active development and requirements in their marketing line-up. This emphasises that the digital era brings certain prevailing conditions. The results of this study demonstrate that the industry of digital marketing is a promising direction to achieve accurate, automated, measurable marketing practices, applicable in a specific career path for the professional with the appropriate.